Pemetaan dan Klasifikasi Kesesuaian Jenis Tanah Terhadap Tanaman Menggunakan Metode Naïve Bayes di Desa Cukilan - Adi Nugroho; Yubal Nugroho Paseneke (AITI, 2022)
Cukilan Village is one of the villages in the Suruh sub-district, Semarang Regency, Central Java. Almost all of the villagers in Cukilan Village work as farmers. Agriculture can generally be done anywhere, but the problem is how to increase and maintain production. For this reason, a classification system is needed to determine the suitability of soil types to plant species. Classification is carried out using the Naive Bayes method. After doing the calculations, it was found that the soil types of brown andosol, brown latosol, and reddish brown latosol have the highest suitability. In contrast, the dark brown Mediterranean has the lowest suitability. The classification results are then compared to the production results. Sweet potato plants have 100% suitability for all types of soil, but their production is not optimal. It was found that there are still many factors needed in the process of plant development, such as temperature, pH, fertilization, etc. Therefore, other calculation attributes are required to get maximum results, k. Then the mapping is carried out using a Geographic Information System (GIS), which visualizes agricultural land, drainage routes, and transportation routes.